Membangun Sistem Kearsipan Berkualitas Untuk Mendukung Tata Kelola Kantor Yang Baik Di SD IT Al-Hijrah - Khalisatun Husna; Rasyita Dewi Lubis; Muhammad Arby Fahrezi; Tengku Darmansah (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to analyze building a quality archiving system to support good office governance. The method in this research is a qualitative research method. Interview data was transcribed and reviewed using thematic content analysis. The study reports key data themes that include improving operational efficiency, increasing transparency and accountability. In this way, researchers investigate how teachers can build a quality archiving system to support good office governance. The research results show that implementing an integrated and modern archiving system can reduce human error, speed up access to information, and increase transparency and accountability in office operations. Implementation of this system also plays an important role in increasing administrative efficiency and facilitating the achievement of overall organizational goals.